Women, Guerrillas, and Love : Understanding War in Central America - Rodriguez, Ileana (Book collections on Project MUSE., 1996)
Che Guevaras diary, testimonies by Omar Cabezas and Toms Borge, novels and short stories by Sergio Ramrez and Arturo Ariasare among the works Ilena Rodriguez examines in order to pinpoint the relationship between the collective and woman, and between woman and the nation-state. Women, Guerrillas, and Love challenges current assumptions about the relationship of gender and sexuality to writing and state building during revolutionary moments.